Using the Theory of Planned Behavior to predict pregnant women's intention to engage in regular exercise. (November 2016) - Lee, Ching-Fang; Chiang, I-Chyun; Hwang, Fang-Ming; Chi, Li-Kang; Lin, Hsien-Ming
Abstract: Objective: the objectives of this study were to use the Theory of Planned Behavior (TPB) in order to determine to what degree pregnant women intended to exercise regularly during pregnancy, and then to evaluate the TPB model fit. Design: this study was based on a cross-sectional survey with a tool which was developed specifically for this study. Setting: we identified and invited pregnant women from two medical center hospitals and one certified prenatal center in northern Taiwan to participate. Participants: using purposive sampling, we selected participants who were in at least the 12th week of gestation and did not have a high-risk pregnancy. 621 completed the instrument, their mean age was 31.76 (SD=3.87). Methods: a self-administered instrument was used to determine the firmness of participants' intention to engage in regular exercise during pregnancy. The data were analyzed using SPSS 19.0 software and LISREL 8.72 software. Findings: of the pregnant women in our study, 64.2% were found to be likely to exercise regularly up until delivery. The TPB was used to arrive at specific findings with regard to "intention to exercise regularly during pregnancy." Our participants demonstrated a positive intention to exercise regularly, a positive attitude (ATT), positive subjective norms (SN) and positive perceived behavioral controls (PBC) during pregnancy. The most influential factor in determining the participants' positive intention to exercise was found to be PBC ( β =0.68, p <0.01), followed by the SN ( β =0.12, p <0.01). The participants' ATT did not significantly influence their intention. Overall, the final model explained 59% of the variation in "intention to exercise regularly." Key conclusion and implication for practice: the most important factor in determining the participants' intention to exercise regularly was PBC, followed by the SN. Medical staff members should be able to help pregnant women overcome obstacles to regular exercise, for example, by assisting in providing appropriate resources. Highlights: The TPB was model fit to predict pregnant women's regular exercise intention. The most influential factor in determining intention to exercise was perceived behavioral control, followed by the subjective norm, while attitude did not significantly influence intention. The TPB model explained 59% of the variation in "intention to exercise regularly" by pregnant women.